Supervisory Report on CSV Monitoring Plan in the Lawra-Jirapa Climate-Smart Villages, Ghana - Nyuor, Anslem Bawayelaazaa (Council for Scientific and Industrial Research, Ghana, 2017)
This report is about the implementation of an M&E monitoring Plan that would allow future monitoring to track the progress of CSA adaptation options currently being implemented in the Lawra and Jirapa Climate-Smart Village site comprising seven communities of these districts located in the Upper West region of Ghana.